2023
DOI: 10.1021/acs.jafc.3c02096
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-Guided Subtraction of MIQOX for Easily Available Isoquinoline Hydrazides as Novel Antifungal Candidates

Abstract: The discovery of novel and easily available leads provides a convincing solution to agrochemical innovation. A bioassay-guided scaffold subtraction of the previous "Chem-Bio Model" isoquinoline-3-oxazoline MIQOX was conducted for identifying the easily available isoquinoline-3-hydrazide as a novel antifungal scaffold. The special and practical potential of this model was demonstrated by a phenotypic antifungal bioassay, molecular docking, and cross-resistance evaluation. A panel of antifungal leads (LW2, LW3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Furthermore, current research reveals that regardless of the inhibitor type, be it organic small molecules, peptides, or proteins, as well as the different target sites (histone deacetylase, succinate dehydrogenase, pyruvate kinase), inhibitors consistently exhibit a more pronounced inhibitory effect on spore germination rather than mycelium growth in B. cinerea . The results of this study are entirely consistent with the literature, suggesting that the observed variations in inhibition effects are not directly associated with the Chitinase target of the DBA inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, current research reveals that regardless of the inhibitor type, be it organic small molecules, peptides, or proteins, as well as the different target sites (histone deacetylase, succinate dehydrogenase, pyruvate kinase), inhibitors consistently exhibit a more pronounced inhibitory effect on spore germination rather than mycelium growth in B. cinerea . The results of this study are entirely consistent with the literature, suggesting that the observed variations in inhibition effects are not directly associated with the Chitinase target of the DBA inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…By using the mycelial growth inhibition method, , the effective concentration for 50% inhibition (EC 50 ) was calculated for the promising compounds (Table S5). The target compounds were dissolved in DMSO and added to PDA medium to give the desired concentrations.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…We used the same method to prepare other required medications. In vivo antifungal activity was tested using reported methods [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%